Synthes and characterisation of wterborne plyurethane ahesives from hdroxyl terminated ntural rbber - Kaenhin L; Campistron I; Klinpituksa P; Laguerre A; Pilard JF; Rungvichaniwat A; Saetung A (Journal of Rubber Research, 2012)
Waterborne polyurethane adhesives weresynthesised by an isocyanate terminated polyurethane prepolymer process using 2,2-bis (hydroxymethyl) propionic acid (DMPA) as an internal emulsifier and chain extension by 1,4- diaminobutane. The different characteristics polyols such as hydroxyl terminated natural rubber (HT) with various number average molecular weight(Mn) at 600 (HT600) and 100 g/mol (HT1000) and epoxidised HT (eHT) with 10 (10eHT) and 37 (37 eHT) percentages of epoxidation were synthesised from natural rubber latex (NRL) for preparing the WPUA. Fourier transform infrared spectroscopy (FTIR) and proton nuclear magnetic resonance spectroscopy (H-NMR) techniwues were used to characterise the chemical structures. The pH value, mean particle size, viscosity, glass transition temperature (Tg), T-peel strength and lap shearstrength of the WPUAs were measured. The WPUAs had pH values of about 7.80 to 8.50. The mean particle size of the WPUAs depended on the DMPA content. At higher DMPA content, a smaller mean particle size was obtained. The Tg of WPUAs exhibited the same trend values of HT and eHT. T-peel strength and lap shear strenth of adhesives were measured by bonding of leather to leather. It was found that WPUA600 and WPUA1000 showed good adhesion. thus, HT and eHT prepared from NRL can be used to prepare WPUA for the footwear industry.
Keywords: Hydroxyl terminated natural rubber; polyurethane dispersion; waterborne polyurethane